The comparison of the effect of curcumin with nystatin on inhibition level of Candida albicans - Nosratzehi T; Nosratzehi M; Nosratzehi S; Lotfi F (Dove Medical Press, 2019)
Tahereh Nosratzehi,1 Mahin Nosratzehi,2 Shahin Nosratzehi,3 Fatemeh Lotfi41Dental Research Center and Department of Oral Medicine, School of Dentistry, Zahedan University of Medical Sciences, Zahedan, Iran; 2Department of Endocrinology, Zahedan University of Medical Sciences, Zahedan, Iran; 3Department of Endocrinology and Metabolism Fellowship, Shahid Beheshti University of Medical Sciences, Tehran, Iran; 4School of Dentistry, Zahedan University of Medical Sciences, Zahedan, IranCorrespondence: Tahereh NosratzehiDepartment of Oral Medicine, Oral and Dental Disease Research Center, Zahedan University of Medical Sciences, Zahedan, IranTel +09153480151Email Nosratzehim@yahoo.comBackground: Curcumin is a kind of medicinal plant, a member of the ginger family, Zingiberaceae. As the herbal medicine has been globally demanded in recent years and due to the anti-viral, anti-inflammatory, and antifungal properties of curcumin, the present study aimed to compare the inhibitory effect of curcumin with that of nystatin on Candida albicans growth.Methods: In this experimental study, the antifungal effect of curcumin on Candida albicans was evaluated. Candida albicans is cultivated in Agar Sabuard medium containing chlorophenic, 10-series of curcumin extract, and one 10-series of a disc impregnated with nystatin. Inside of each plate, one disc of herbal extract, one disc of nystatin as a positive control, one disc of methanol and one empty disc as negative control were placed, after 24 hrs, the inhibitory zone diameter of the herbal extract was compared with that of positive control using Mann–Whitney.Results: The mean of inhibitory zone diameter in nystatin and curcumin was 1.04±20.46 and 1.36±0.89 mm, respectively. Mann–Whitney test shows a significant difference between the inhibitory zone diameter of these materials (P<0.001).Conclusion: The results of this study suggested that curcumin extract did not have any effect on the inhibition of Candida albicans in laboratory environment.Keywords: curcumin extract, nystatin, Candida albicans